Classification of Networks in Higher Education: A Marketing Analysis of the Club of Ten (Russia) - Irina V. (National Research Mordova State University, 2018)
Introduction: the networking as a development practice in business has not yet become widespread. Moreover, there are very few studies of network interactions in the field of science and education. Advances in marketing evaluation of network entities are very rare. The goal of this article is to develop methodological criteria for such an assessment. These methods were tested on findings from the network partnership established by federal universities in Russia. Materials and Methods: to study and generalise real-world experience, a case study method was used, which the authors understand as an empirical research method aimed at studying phenomena in real time and in the context of real life. Results: the authors proposed a comprehensive methodology for estimation of networks. The application of this method of analysis enabled identification of the key problems and barriers to the implementation of the project. One of the main problems is the lack of marketing analysis, lack of understanding of its target audience, and, accordingly, the lack of a transparent vision of development. Besides, the authors have developed a classification of network partnerships. Тhe analysis empowers classification of the network of Russian universities as an inter-organisational polycentric partnership of a quasi-integration type, based on a neoclassical contract with relational elements. The analysis of the network development has revealed significant deviations of the results from the initially claimed ones. Discussion and Conclusions: the theoretical significance of the work consists in the application of the network theory to an atypical object for the economic theory, i.e. the analysis of the sphere of higher education. Practical significance lies in the possibility of application of results obtained through real projects in real-time mode. The results of the study are applicable to educational systems for practically all countries with a transition type of economic and educational systems.